1997
DOI: 10.1002/(sici)1096-9896(199712)183:4<477::aid-path955>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects ofL-arginine after liver ischaemia/reperfusion injury in a pig model

Abstract: Hepatic ischaemia/reperfusion is characterized by circulatory and metabolic derangement, liver dysfunction, and tissue damage. To evaluate the role of L‐arginine, a substrate of nitric oxide, in ischaemia/reperfusion injury, total liver ischaemia was induced for 120 min in 22 Landrace×Large White female pigs, which were randomly assigned to a treatment group (10 animals) or a control group (12 animals). An L‐arginine bolus (540 mg/kg i.v.) was administered to the treatment group 1 h before clamping the hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This is consistent with the results of other studies. For example, the administration of Arg reduces damage to liver tissue after ischaemia injury [13]. In addition, it has been reported that Arg could protect rats with liver cirrhosis from acute ammonia intoxication [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of other studies. For example, the administration of Arg reduces damage to liver tissue after ischaemia injury [13]. In addition, it has been reported that Arg could protect rats with liver cirrhosis from acute ammonia intoxication [28].…”
Section: Discussionmentioning
confidence: 99%
“…Arg deficiency can result in hyperammonemia, and intestinal and immunological dysfunction [11,12]. The administration of Arg reduces damage to liver tissue after ischaemia injury [13]. Urea synthesis from primary hepatocytes seems to be a valid viability indicator, since mitochondrial transmembrane transport of the urea cycle intermediates ornithine and citrulline is involved in the urea cycle [14].…”
Section: Introductionmentioning
confidence: 99%